Evaluation of currently registered herbicides for fall bearing year red sorrel - White, Scott N; Menapati, Rakesh; McLean, Nancy (Canadian journal of plant science, 2021)
Red sorrel is a common creeping herbaceous, perennial weed species in lowbush blueberry fields and reproduces asexually via ramets from creeping roots. Ramets emerge throughout the season but remain vegetative due to a vernalisation requirement for flowering. This weed may therefore be managed with fall herbicide applications, but few currently registered herbicides have been evaluated for fall red sorrel management in lowbush blueberry. The objectives of this research were to (i) determine the effect of various herbicide treatments on red sorrel shoot and root biomass in the greenhouse, (ii) determine the effect of fall bearing year herbicide applications on overwintered red sorrel ramet density in the field, (iii) determine if reduced overwintered ramet density reduces flowering ramet density in the field, and (iv) estimate the potential for red sorrel to recover from fall bearing year herbicide applications. Dicamba, tribenuron-methyl, and glufosinate reduced red sorrel shoot and root biomass in the greenhouse and reduced overwintered ramet density in the field. Clopyralid, sulfentra-zone, and flumioxazin reduced shoot and root biomass in the greenhouse but exhibited limited efficacy in the field. Nicosulfuron + rimsulfuron and glyphosate were ineffective in both the greenhouse and field. Dichlobenil and pronamide reduced overwintered ramet density in the field. Reduction of overwintered ramet density did not consistently reduce flowering ramet density. Dichlobenil reduced seedling density at two sites, but no herbicide consistently reduced summer non-bearing year ramet density. Fall herbicide applications alone, therefore, do not appear to maintain red sorrel suppression in lowbush blueberry fields.